Effects of free-play or introducing artificial rules on tactical behavior based on soccer-team lines: A pilot study - Gonzalez-Artetxe, A.; Los Arcos, A.; Folgado, H.; Rico-González, M.; Pino-Ortega, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Team-lines structures are particular subsystems determined strategically by the formation chosen by the team coach, and despite its relevance, no study has analyzed training effects on tactical behavior based on team lines. This study aimed to assess the effects of modified games playing freely and introducing artificial rules on tactical behavior based on team lines during the team-possession game phase in two youth-soccer categories. Two Spanish under-14s (U-14s: n = 16) and under-16s (U-16s: n = 16) teams took part in the study. Each team was divided into two groups, free-play and conditioned, that faced each other during three 7-min eight-on-eight games in four training sessions. The free-play group played freely without restrictions, while the conditioned group played constrained by artificial rules (i.e. a minimum number of touches, no return pass allowed, forward pass after a back pass) that modified the cooperative motor interactions between teammates. Tactical behavior was assessed by the three geometrical primitives` representations (i.e. node: change in the centroid position (CCP), line: interpersonal distance between teammates (dyads), and area: surface area (SA)) and their time series approximate entropy (ApEn) normalized measures in subgroups based on team lines (goalkeeper - defenders, defenders - midfielders, and midfielders - forward) before and after the training intervention in an eight-on-eight game using a local positioning system (LPS). The results suggest that the short-term training intervention affected considerably (i.e. Cohen`s d= moderate) U-14s team lines` behavior, especially those who played freely. On the other hand, U-16s` tactical behavior based on team lines barely changed (i.e. Cohen`s d= small). It seems that playing freely for several training sessions could strengthen the tactical behavior of each line, enhancing team lines` regularity in youth-soccer categories.